The short-term relation between load and acute psychophysiological responses in football: a meta-analysis and methodological considerations - Brauers, J. J.; Den Hartigh, R. J. R.; Klooster, D.; Oosterveld, F. G. J.; Lemmink, K. A. P. M.; Brink, M. S. (Science and Medicine in Football, 2026)
Relations between load and acute psychophysiological responses have been widely studied in football. However, due to the large heterogeneity in contexts, operationalization, and results, the direction and strength of these relations remain unclear. In this meta-analysis, we examine the relation between load and typical acute (i.e. within one week) responses - wellbeing, recovery, and heart rate measures - in football players from all football codes (soccer, rugby, futsal, American football, and Australian rules football). We consulted PubMed, Web of Science, and CINAHL up to the 19th of June 2024, and included 62 articles and 1,474 participants in the meta-analysis. Subsequently, we estimated 12 meta-analysis models and applied meta-regression models to explore the influence of several moderators. Significant relations were found between load and overall wellbeing (r = -0.33 [95%CI: -0.48; -0.19]), muscle soreness (r = -0.36 [95%CI: -0.49; -0.24]), fatigue (r = -0.41 [95%CI: -0.56; -0.26]), sleep quality (r = -0.21 [95%CI: -0.31; -0.10]), and stress (r = -0.16 [95%CI: -0.26; -0.06]). Given the high risk of bias, inconsistency (wide prediction intervals), and imprecision, the certainty in these findings based on the GRADE assessment is very low. Additionally, the high risk of bias scores indicates that the overall quality of the included studies is low. In conclusion, this meta-analysis provides comprehensive information on the acute responses of the athlete to load, and directions for improvement of the quality of future studies.